Quantifying the relative irreplaceability of important bird and biodiversity areas. Issue 2 (21st October 2015) - Di Marco, Moreno; Brooks, Thomas; Cuttelod, Annabelle; Fishpool, Lincoln D.C.; Rondinini, Carlo; Smith, Robert J.; Bennun, Leon; Butchart, Stuart H.M.; Ferrier, Simon; Foppen, Ruud P.B.; Joppa, Lucas; Juffe‐Bignoli, Diego; et al.
Abstract: World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.